2018
DOI: 10.1016/j.pedneo.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered regional and circuit resting-state activity in patients with occult spastic diplegic cerebral palsy

Abstract: Resting-state regional brain activities and FC changes in the patients with occult SDCP exhibited a special distribution pattern, which is consistent with the pathology of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Li et al [ 56 ] reported that GSR strengthens association between resting-state functional connectivity and behavior in young healthy adults. And in some studies [ 57 , 58 ], the authors regressed out global signal as a nuisance variable to reduce the effects of nonneuronal BOLD fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 56 ] reported that GSR strengthens association between resting-state functional connectivity and behavior in young healthy adults. And in some studies [ 57 , 58 ], the authors regressed out global signal as a nuisance variable to reduce the effects of nonneuronal BOLD fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the resting-state fMRI scanning is simple and easy to execute for these children [ 31 ]. Functional connectivity, referring to an analysis for identifying spatial patterns of coherent BOLD activity in distributed brain regions, has been used to detect the abnormal pathways (e.g., somatosensory, motor, and thalamocortical pathway) in children with CP using resting-state fMRI data [ 22 , 32 , 33 ]. For defining distinct modes of long-distance interactions, independent component analysis (ICA) has been a popular method to generate resting-state networks (RSNs) [ 34 , 35 ], and resting-state functional network connectivity (FNC) [ 36 ] can be used to represent the temporal correlation among these RSNs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, rs-fMRI has provided unique insights on how the perinatal brain injuries in youth with CP impact the integrity of the RSNs [25][26][27][28][29]. These studies have revealed that youth with a spastic diplegic presentation have higher FC within the sensorimotor cortices than their neurotypical peers [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, rs-fMRI has provided unique insights on how the perinatal brain injuries in youth with CP impact the integrity of the RSNs [25][26][27][28][29]. These studies have revealed that youth with a spastic diplegic presentation have higher FC within the sensorimotor cortices than their neurotypical peers [25,26]. In contrast, FC between the sensorimotor cortex and the cerebellum, contralateral sensorimotor cortex, cingulate motor area, visual cortices and parietal lobes have been described as weaker in youth with CP compared to controls [25,28,30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation